A Comparative Study of the Nature of Ransom and Wise from the Perspective of Feyz Kashani and Imam Khomeini - Kazemi Nasab, Masoumeh (2021)
The nature of ransom and the issue of guaranteeing wisdom is one of the important issues in jurisprudence and law; various views have been expressed about it so far. The connection between the two goes back to the nature of ransom; if we consider ransom as a mere punishment, it is in conflict with the principle of personal punishment but if we consider the ransom as compensation, or consider it dual in nature, there will be no conflict between this rule and the principle. In this article, an attempt has been made to the nature of ransom and wisdom should be examined from the perspective of Feyz Kashani and Imam Khomeini, the basic question that arises in this regard is that; how can the views of Feyz Kashani and Imam Khomeini regarding the nature of ransom and wisdom be evaluated? The present article is an analytical description and has used the library method to examine the question. The results of the article indicate that; from the point of view of Feyz Kashani and also Imam Khomeini, ransom has a dual nature; because ransom, as an independent legal entity, has a civil aspect and compensates the damages and losses inflicted on the victim or his parents, on the other hand, it has a criminal aspect and provides the means of punishment and learning lessons for the perpetrator. Also, the payment made by the wise has been accepted from the point of view of Feyz Kashani and Imam Khomeini. Accordingly, whenever a non-Muslim citizen from Dhimma commits a pure mistake and is unable to pay the ransom, whenever a murderer commits premeditated murder and then escapes and he and his relatives have no money, whenever the person who committed the murder of a pure mistake does not have the wisdom of paying the wise ransom, or if his wisdom is incapable, the payment of ransom will be the responsibility of the treasury. From Imam Khomeini's point of view, the most important basis of the government's responsibility as a wise man is the rule of "Al-Kharaj bi Al-Dhiman" but Feyz Kashani has not discussed this issue.